Allelopathic Effects of Aqueous Extract from Satureja thymbra L. on Seed Germination and Seedling Growth of Pinus halepensis Mill. and Ceratonia siliqua L - Masoud, Moussa; A. K. Omar, Mohamed; A. Abugarsa, Saleh (Libyan Journal of Science &Technology, 2022)
The objective of this study was to determine the impact of allelopathic potentials of aqueous extract of Satureja thymbra L. aerial parts on seed germination of Ceratonia siliqua L. and early growth seedling of Pinus halepensis Mill. and Ceratonia siliqua L. Satureja thymbra L. aerial parts were collected from Al-Jabal Al-Akhdar, Libya and collected aerial parts were dried and powdered. The treatments included 100%, 50% and 25% aqueous extracts along with water as a control. One-way analysis of variance (ANOVA) was performed and Regression analysis between treatments vs. root length, shoot length, and number of leaves among Pinus halepensis Mill and Ceratonia siliqua L. were done. The results showed seed germination of Ceratonia siliqua decreased by increasing extract concentration. The highest and lowest seed germination was belonged to control and 100 % extract respectively. In addition, the result showed a significant difference between treatments in root length and the number of leaves of both species. The LSD test showed that root length and number of leaves of Pinus halepensis Mill. and Ceratonia siliqua L. at treatments of 25%, 50% and 100% was significantly different from control. The regression analysis between root length, and number of leaves in Pinus halepensis Mill. and Ceratonia siliqua L. were significantly reduced with the increase in the extract concentration. The results demonstrate that previously mentioned extracts have inhibitory effects on the growth of roots and shoots of Pinus halepensis Mill. and Ceratonia silique L. Thus, it is recommended to use from residual of medicinal plant or select them in crop rotation systems to weed by allelochemicals compounds.